قبل از اسلام شہر مکہ میں معاہدات کی نوعیت و حیثیت: Treaties and Their Role in Pre-Islamic Meccan Society - Nadeem, Dr. Muhammad Abid (Al-Irfan, 2025)
By nature Human Being are social. All progress made by them since human life on this planet earth is because of the social interaction with others. To strengthen this mutual interaction man has always devised some strategy so that the societal and cultural progress may be induced. There is a great variety in the agreements in Makkan society before Islam. The agreements were for the purpose to abstain from indulging any war like situation, to stop the wars, to call others to help in any battle, to get consensus on the sanctity of some thing, to live together in a peaceful manner, to enhance the trade activities and to for the purpose to search the allies. Sometimes, a special agreement called Wilā was concluded to be the part of some powerful tribe. The purpose of all such agreements was to bring harmony in the society and to develop mutual relations. The Makkan state had been established before the advent of Islam. The Makkan society has been strengthened through the establishment of Dār alNnadwah. To perfom various functions, so many types of agreements like Wilā, Ḥilf and Ṣulḥ were concluded so that a cooperative atmosphere may be created in any untoward situation. Muhammad (PBUH) also involved himself and abided by such agreements. Even after his migration to Madina, once he said that he would prefer to be the part of agreement like Ḥilf al Fuḍūl over gettine the red camels. In this dissertation, the importance and categories of the agreements in the Makka will be focused on.